Acquired Neonatal Brachial Plexus Palsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
Three infants presenting at 3, 15, and 21 days of age with brachial-plexus neuropathy were found to have a group-B streptococcal osteomyelitis, as reported from the British Columbia's Children's Hospital, Vancouver, Canada.